(untitled) (Research, Society and Development, 2021)
In the legal-procedural area, one must observe the entire structure of principles stamped in the text of the Brazilian Federal Constitution, particularly those listed to the level of human rights, incorporated by the national order and conceived from the aspect of fundamental rights, which will govern the entire framework of legal and social relations, taking into account the universality of such precepts and the guarantee of access to justice. In this context of standard principles, three of them stand out, namely due process, contradictory and broad defense. However, in everyday legal pragmatism, it is perceived that little attention is methodically directed to the distinction between such statements, especially with regard to contradictory and broad defense, in view of the constitutional textual disposition itself, which allocates them in a fundamental and joint writing. Therefore, based on the qualitative scientific methodology, based on a bibliographic review, carried out foremostly by doctrinal and jurisprudential analysis, this article has the objective of presenting the guidelines that evidence the ontological difference between due process, contradictory and broad defense, according to the guidelines derived from the legal reflection of interpreters and applicators of positive law, considering the constitutional need for unitary understanding of the precepts of the Brazilian Major Text.